Bioresorbable hydrogels prepared by photo-initiated crosslinking of diacrylated PTMC-PEG-PTMC triblock copolymers as potential carrier of antitumor drugs - Yuandou Wang; Laishun Xi; Baogang Zhang; Qingzhen Zhu; Feng Su; Katarzyna Jelonek; Arkadiusz Orchel; Janusz Kasperczyk; Suming Li (Elsevier, 2020)
PTMC-PEG-PTMC triblock copolymers were prepared by ring-opening polymerization of trimethylene carbonate (TMC) in the presence of dihydroxylated poly(ethylene glycol) (PEG) with Mn of 6000 and 10,000 as macro-initiator. The copolymers with different PTMC block Lengths and the two PEGs were end functionalized with acryloyl chloride. The resulting diacrylated PEG-PTMC-DA and PEG-DA were characterized by using NMR, GPC and DSC. The degree of substitution of end groups varied from 50.0 to 65.1%. Hydrogels were prepared by photo-crosslinking PEG-PTMC-DA and PEG-DA in aqueous solution using a water soluble photo-initiator under visible light irradiation. The effects of PTMC and PEG block lengths and degree of substitution on the swelling and weight loss of hydrogels were determined. Higher degree of substitution leads to higher crosslinking density, and thus to lower degree of swelling and weight loss. Similarly, higher PTMC block length also leads to lower degree of swelling and weight loss. Freeze dried hydrogels exhibit a highly porous structure with pore sizes from 20 to 100 µm.The biocompatibility of hydrogels was evaluated by MTT assay, hemolysis test, and dynamic clotting time measurements. Results show that the various hydrogels present outstanding cyto- and hemo-compatibility. Doxorubicin was taken as a model drug to evaluate the potential of PEG-PTMC-DA and PEG-DA hydrogels as drug carrier. An initial burst release was observed in all cases, followed by slower release up to more than 90%. The release rate is strongly dependent on the degree of swelling. The higher the degree of swelling, the faster the release rate. Finally, the effect of drug loaded hydrogels on SKBR-3 tumor cells was evaluated in comparison with free drug. Similar cyto-toxicity was obtained for drug loaded hydrogels and free drug at comparable drug concentrations. Therefore, injectable PEG-PTMC-DA hydrogels with outstanding biocompatibility and drug release properties could be most promising as bioresorbable carrier of hydrophilic drugs. Keywords: Bioresorbable, Hydrogels, Poly(trimethylene carbonate), Drug release, Doxorubicin, Biocompatibility, Cyto-toxicity